Clod by clod, drop by drop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
All these increases in crop yields that we need to make, where will they come from? Mud, sweat and tears, and selected inputs, for starters. Plus lots more tweaking of what we can do with soil and water.Remember that bone-shuddering statistic in...